A metabolomics study of the inhibitory effect of 17-beta-estradiol on osteoclast proliferation and differentiation. Issue 2 (4th December 2014) - Liu, Xiaoyan; Liu, Yanqiu; Cheng, Mengchun; Zhang, Xiaozhe; Xiao, Hongbin
Abstract : A metabolomics approach was used to explore metabolic alterations during estradiol induced inhibition of osteoclast (RAW 264.7) proliferation and differentiation. Abstract : Estradiol is a major drug used clinically to alleviate osteoporosis, partly through inhibition of the activity of osteoclasts, which play a crucial role in bone resorption. So far, little is known about the effects of estradiol on osteoclast metabolism. In this study, ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC/MS)-based metabolomics strategy was used to investigate the metabolite response to 17β-estradiol in mouse osteoclast RAW264.7, a commonly used cell model for studying osteoporosis. Our results showed that the application of estradiol altered the levels of 27 intracellular metabolites, including lysophosphatidylcholines (LysoPCs), other lipids and amino acid derivants. The changes of all the 27 metabolites were observed in the study of estradiol induced osteoclast proliferation inhibition (1 μM estradiol applied), while the changes of only 18 metabolites were observed in the study of differentiation inhibition (0.1 μM estradiol applied). Further pathway impact analysis determined glycerophospholipid metabolism as the main potential target pathway of estradiol, which was further confirmed by LCAT (phosphatidylcholine-sterol acyltransferase) activity changes and lipid peroxidative product (MDA, methane dicarboxylic aldehyde) changes caused by estradiol. Additionally, we found that estradiol significantly decreased intracellular oxidative stress during cell proliferation but not during cell differentiation. Our study suggested that estradiol generated a highly condition-dependent influence on osteoclast metabolism.